Enhancement increasing the productivity of the traditional herbal “Jamu Mak Lin” through a community partnership program - Hapsari, Ira Maya; Akhmadi, Amin Nur; Tulodo, Rizki Prasetyo; Santosa, Irfan (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2025)
Background: The traditional home-based herbal medicine industry,” Jamu Mak Lin” faces challenges, including traditional herbal medicine production methods on traditional equipment. The packaging and labels of herbal medicine are not registered. There is a scarcity of effective door-to-door marketing strategies. A lack of good management and financial accountability systems. Contribution: The main objective is to increase the productivity of “Jamu Mak Lin” traditional herbs through improvements in production processes and equipment, financial management, and marketing strategies. Method: The method applied is Participatory Action Research (PAR), consisting of both hard and soft programs. Results: The results show a significant improvement in liquid herb production, reaching 150 bottles of 350 mL (approximately 52.5 liters), with an estimated increase in productivity and profit of up to 85% per day. In addition, “Jamu Mak Lin” traditional herbal products have been registered for halal certification, and the packaging design has been improved to be more elegant, hygienic, and readable. Conclusion: Through this community partnership program, the productivity and income of “Jamu Mak Lin” traditional herbal products have significantly increased. The next program’s sustainability is achieved by diversifying herbal medicine dipping and herbal medicine cafes.